Trends in Cognitive Function Among Chinese Elderly From 1998 to 2018: An Age-Period-Cohort Analysis - Hu, Xiaoqian; Gu, Shuyan; Zhen, Xuemei; Sun, Xueshan; Gu, Yuxuan; Dong, Hengjin (Frontiers in Public Health, 2021)
Objectives: To investigate the age, period, and cohort (APC) effects on trends in cognitive function among the Chinese elderly, and to explore how gender gaps in cognitive function change with age, period, and cohort. Methods: This study used data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) from 1998 to 2018, including 90432 participants aged above 65 years old. The measurement of cognitive function was the score of the Mini Mental State Examination (MMSE). Cross-classified random-effects models were conducted to investigate age, period, and cohort trends in cognitive function. Results: MMSE scores decreased with age at an increasing rate. While the cohort effect was nearly stable, the period effect demonstrated a downward trend from 1998 to 2002 followed by a nearly flat line. Females were associated with lower MMSE scores than males. When age increased, the gender gaps in MMSE scores further increased. The period-based gender gaps in MMSE scores diverged throughout the 20 years, while the cohort-based gender disparities in MMSE scores converged with successive cohorts. Conclusions: Age, period, and cohort had different and independent effects on cognitive function among the Chinese elderly. The age effect was stronger compared to period and cohort effects. The gender disparities in cognitive function increased with age and period and decreased with successive cohorts.